STRUCTURE COMMUNITY OF MANGROVE IN THE VILLAGE A PANTAI CERMIN KIRI DISTRICTS PANTAI CERMIN REGENCY OF SERDANG BEDAGAI THE PROVINCE OF NORTH SUMATRA - Andreas Situmorang; Aras Mulyadi; Efriyeldi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Study was conducted in february 2017. This report aims to understand structure community of mangrove in the village Pantai Cermin kiri in the Pantai Cermin North Sumatra. Methods used in research is method of surveying. The research station based on human activity. In every station divided into 3 transects with long transects 50 m lead from the sea to land. The number of a plot used by 27, with each size 10 x 10 m2 to tree level, 5 x 5 m m2 to the saplings, and 2 x 2m2 to level seedling. The result of this research found 7 mangrove species in the village Pantai Cermin kiri. Vegetation that dominated is Rhizophora apiculata with INP of 300 %. A condition of vegetation in the village Pantai Cermin Kiri in the shore Pantai Cermin mangrove are forest area is still in good with the density of of 2377,78 tree / ha.Kata Kunci: Village Pantai Cermin Kiri, Structure Community, mangrove.